2014
DOI: 10.1186/1546-0096-12-12
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the vasa vasorum in the development of vasculitis in animal model of Kawasaki disease

Abstract: BackgroundKawasaki Disease (KD) involves a diffuse and systemic vasculitis of unknown etiology that mainly affects infants and children. Although a considerable number of analyses of the clinical, histopathological and molecular biological details underlying the mechanism responsible for the development of coronary arterial lesions, it is still poorly understood.The purpose of this study was to analyze the state of angiogenesis, vasculogenesis and the distribution of blood vessels using an animal model of KD l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Several studies indicate that depression and anxiety rates are high in youth from many chronic disease groups, 6, 10, 12 but little is known about the differences between these groups. As a first step in looking beyond the known associations of depression and anxiety with adolescent age, female sex and the presence of chronic disease, we utilized a matched cross-sectional analysis to compare risk factors for depression and anxiety in two pediatric chronic disease cohorts of similar age group and sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate that depression and anxiety rates are high in youth from many chronic disease groups, 6, 10, 12 but little is known about the differences between these groups. As a first step in looking beyond the known associations of depression and anxiety with adolescent age, female sex and the presence of chronic disease, we utilized a matched cross-sectional analysis to compare risk factors for depression and anxiety in two pediatric chronic disease cohorts of similar age group and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary care providers have been identified as mediators for mental health intervention in youth in general, 45 those with chronic disease like SLE/MCTD typically see their subspecialty providers more often 6 and may benefit from intervention at subspecialty care sites. 6 Recent literature indicating successful implementation of depression screening in youth with T1D at outpatient diabetes clinic visits 46 is encouraging for feasibility of subspecialty-based intervention, potentially increasing mental health treatment rates, reducing disparities in care and improving outcomes. Further investigation of effective strategies for mental health symptom recognition and intervention for youth with chronic disease is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though lymphatic channels are not found in the media of normal and arteriosclerotic coronary arteries, it does not exclude soluble antigen or even rare antigen-presenting cells from extravasation into the adventitia where they may collect into perivascular lymphatic vessels. 75 It has not been determined whether direct introduction of foreign antigens into the arterial media can immunize the recipient, although antigen expression in other avascular immunoprivileged tissues can succeed or fail to activate immunity depending on the experimental conditions. 76,77 A reasonable assumption for medial immunoprivilege is an elastin barrier to cellular traffic.…”
Section: Mechanisms Of Medial Immunoprivilegementioning
confidence: 99%
“…In fact, Takahashi et al demonstrated that the inflammatory changes in the adventitia occur prior to the changes in the intima in various animal models of KD vasculitis (45). Furthermore, Hamaoka-Okamoto et al revealed that the proliferation of adventitial VV was accompanied by an increase in the inflammation confirmed by a scanning electron microscope (SEM) in a murine model of KD vasculitis (46). Additionally, in specimens of coronary arteries from KD patients with CAAs, Suzuki et al showed that the overexpression of GFs was observed in the microvessels of the thick intima and there was an expanded VV network in the adventitia (32).…”
Section: Carotid Contrast-enhanced Ultrasonography (Ceus)mentioning
confidence: 96%